Pregabalin - Eloghosa Ohonba (BioScientist: The Salford Biomedicine Society Magazine, 2024)
Pregabalin, a GABA analog originally developed as an anticonvulsant, has recently gained widespread use in managing neuropathic pain and fibromyalgia. Despite its therapeutic evidence, recent studies suggest that pregabalin has abuse potential especially among individuals with prior history of drug abuse and those using opioids. While pregabalin is a controlled substance in the UK and USA, its misuse continues to rise. Case reports show that even patients without a history of substance abuse can experience withdrawal symptoms, including agitation and insomnia, upon discontinuation, suggesting the potential for dependence even at therapeutic doses. This article examines the pharmacological action of pregabalin, the pattern of abuse and how the issue of pregabalin abuse and misuse can be addressed by prescribers and healthcare policy makers.
Keywords: pregabalin; Lyrica; neuropathic pain; fibromyalgia; epilepsy; abuse potential; dependence; withdrawal symptoms; prescription regulations; healthcare responsibility